PENGARUH RADIASI MATAHARI DAN JENIS MATERIAL COIL PADA PV-MODULE SOLAR ELECTRIC COOKER - Asrori Asrori; Harie S. Jaya (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
Global energy needs are increasing, while world energy reserves derived from fossils are dwindling. Therefore, a breakthrough is needed to develop green technology based on renewable energy, especially in the household sector. Indonesia is located on the equator so it has great potential to explore solar energy sources. This study aims to analyze the effect of the type of coil heater material and the level of solar radiation on the PV module solar electric cooker. Testing carried out in the Solar Energy Lab., Mechanical Engineering, State Polytechnic of Malang (7°56ʼ36.4ˮS ; 112°36ʼ49.6ˮE). The method used is true experimental using three material types based on their thermal conductivity, namely copper, aluminum, and nickel as well as the change in solar radiation on the heat of solar electric cooker generated by the PV module. The results showed that there was an effect of the parameters of thermal conductivity and changes in solar radiation on the heat generated by the PV module solar electric cooker. In the nickel coil test, it can reach a temperature of 769°C at a solar radiation of 875.9 W/m2. Testing the aluminum coil obtained a temperature of 191°C at a solar radiation level of 931.4 W/m2, and a copper coil could produce a temperature of 169°C at a solar radiation level of 855.6 W/m2